OPTIMALISASI PARIWISATA BERBASIS MASYARAKAT MELALUI KELEMBAGAAN KEWIRAUSAHAAN DI DESA WISATA KAMPUNG KELEMBAK BATAM - Tirta Mulyadi (LPPM Universitas Bina Bangsa, 2023)
The institutional entrepreneurship strategy to optimize community-based tourism in Kampung Kelembak Tourism Village is divided into ideas and discourse. Strategic ideas are needed in managing Kampung Kelembak Tourism Village. By relying on community-based entrepreneurship. Of course, it is hoped that the development of Kampung Kelembak Tourism Village will have a direct influence on the community's economy. Collaboration with universities will accelerate this goal. Entrepreneurship will create product innovation as well as environmental preservation and cultural preservation programs with the community can be implemented. These strategic ideas must be implemented through discourses. There are two discourses to convey ideas, namely coordinative discourse and communicative discourse. communicative. Strategic ideas must be conveyed, communicated, negotiated elaborated, and sharpened in coordinative discourse. This research also shows that synchronization actions are required in the deliberation forum for the management of tourist villages on a regular basis. The deliberation forum is conducted at the beginning and on an ongoing basis to ensure the effectiveness of tourism village management. This is necessary to evaluate the implementation of activities and management of tourist villages to make them more controllable. more controllable.